Pengaruh Profitabilitas, Likuiditas, dan Struktur Modal Terhadap Nilai Perusahaan Makanan dan Minuman yang Terdaftar di BEI - Bintang Sridevi Simangunsong; M. Khoiri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The value of companies in food and beverage companies listed on the IDX varied in the 2016 – 2020 period. The purpose of this review is to see whether profitability (Return On Assets), liquidity (Current Ratio), and capital structure on the value of companies in the food and beverage sector are significant. has been listed on the Indonesia Stock Exchange from 2016 to 2020. Profitability is estimated by ROA, Liquidity is estimated by the Current Ratio, Capital structure is estimated by Debt to Equity Ratio and company value is estimated by Price to Book Value. The number of samples in this study were 10 food and beverage companies listed on the Indonesia Stock Exchange. Purposive sampling method in this study was used in determining the sample. The data analysis technique used multiple linear regression analysis with the help of SPSS version 26. This review resulted in profitability having a significant effect on firm value, indicated by a sig value of 0.000 <0.05. The liquidity indicator has no significant effect on firm value, indicated by a significant value of 0.066 > 0.05. The capital structure variable does not have a significant effect on the value of food and beverage companies listed on the IDX for the period 2016 – 2020 with a significant value of 0.062 > 0.05. And simultaneously profitability, liquidity and capital structure affect the value of food and beverage companies listed on the IDX for the period 2016 – 2020.